2018
DOI: 10.1515/cclm-2018-0541
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study for the evaluation of the reference interval for TSH in Italy (ELAS TSH Italian Study)

Abstract: Background The aims of this study were: (1) to calculate reliable thyroid stimulating hormone (TSH) reference intervals using laboratory databases; (2) to evaluate the relationship between TSH, sex and age values in different large Italian populations. Methods The TSH values stored in the laboratory information system of clinical laboratories of four Italian city hospitals, including 146,801 TSH measurements (with the respective age and sex data of individuals) were taken in consideration. Assuming a log-norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…The reference intervals suggested by manufacturer for TSH (0.49‐4.91 mIU/L), FT4 (0.59‐1.25 ng/dL), FT3 (2.14‐4.21 pg/mL), TT4 (5.44‐11.85 ÎŒg/dL), and TT3 (0.66‐1.61 ng/mL) were calculated on a general population (n = 1316) of approximately equal numbers of male and female individuals with ages ranging from 18 to 86 years. Previously, the reference interval for TSH using new Access TSH 3rd IS assay was also verified in Italian populations, which was 0.362‐5.280 mIU/L . The reference interval in Italian populations is similar to that suggested by the manufacturer.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The reference intervals suggested by manufacturer for TSH (0.49‐4.91 mIU/L), FT4 (0.59‐1.25 ng/dL), FT3 (2.14‐4.21 pg/mL), TT4 (5.44‐11.85 ÎŒg/dL), and TT3 (0.66‐1.61 ng/mL) were calculated on a general population (n = 1316) of approximately equal numbers of male and female individuals with ages ranging from 18 to 86 years. Previously, the reference interval for TSH using new Access TSH 3rd IS assay was also verified in Italian populations, which was 0.362‐5.280 mIU/L . The reference interval in Italian populations is similar to that suggested by the manufacturer.…”
Section: Discussionsupporting
confidence: 61%
“…We only found that the levels of FT3 in subjects with the age of less than 30 years were significantly higher than other groups. However, according to Clerico et al, a negative linear relationship was observed between TSH throughout all interval age values and TSH values in Italian populations tend to decrease with age. These conflicting results may be explained by taking into account the different pathophysiological conditions of the enrolled individuals and the large difference between sample sizes.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This may simply involve excluding values beyond an arbitrary limit, such as those more than 10 times the upper reference limit 13 or involve a statistical test, such as that of Tukey, or others. [14][15][16] Another data pre-processing step that may be used is the exclusion of data from particular referral sites where there is a high likelihood that the patients have significant disease, such as intensive care units and oncology departments. 13,17 It may also be appropriate to exclude data from additional referral sites depending on the analyte of interest, for example lipid and renal clinics.…”
Section: Data Pre-processingmentioning
confidence: 99%